Presentation of a Social Responsibility Measurement Model in Tejarat Bank with a Brand-Centric Approach - Jafari Afshar, Reza; Heidari, Abbas; Jamshidi Avanaki, Mina (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: Nowadays, social responsibility is considered essential for organizations, as it significantly influences various organizational outputs. Many organizations are continually striving to improve their image through the development of their social responsibilities. This study presents a model for measuring social responsibility in Tejarat Bank. Methodology: The research was conducted using a mixed-method approach (qualitative and quantitative). The qualitative sample consisted of 10 experts, and the quantitative sample included 413 managers and specialists from Tejarat Bank, with 203 individuals selected as the statistical sample using a sample size formula. In the qualitative part, an initial model including 3 dimensions, 9 components, and 45 indicators was extracted through interviews with bank experts. Subsequently, the extracted model was tested using structural equation modeling in the LISREL software environment. Findings: Results showed three main dimensions: customer-centricity (including components of responsiveness and service quality), legal and ethical (including stakeholders, employees, community rights, and organizational activities), and environmental focus (including environmental factors, online marketing, and internet service provision). Conclusion: To improve service quality, it is suggested that managers examine the customer experience in all service delivery processes and assess customers’ mental satisfaction. It is also recommended that service delivery channels to customers be standardized, meaning that services received through various means (such as mobile banking, internet banking, etc.) should be uniform, and if a customer begins a service process through one channel, they should be able to continue it through another.